2002
DOI: 10.1002/bit.10501
|View full text |Cite
|
Sign up to set email alerts
|

Improved fuel cell and electrode designs for producing electricity from microbial degradation

Abstract: A new one-compartment fuel cell was composed of a rubber bunged bottle with a center-inserted anode and a window-mounted cathode containing an internal, proton-permeable porcelain layer. This fuel cell design was less expensive and more practical than the conventional two-compartment system, which requires aeration and a ferricyanide solution in the cathode compartment. Three new electrodes containing bound electron mediators including a Mn(4+)-graphite anode, a neutral red (NR) covalently linked woven graphit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
286
0
6

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 613 publications
(306 citation statements)
references
References 20 publications
3
286
0
6
Order By: Relevance
“…An increase of the potential beyond the normal biological boundaries indicates inability of the bacteria to provide electrons at a sufficient rate to avoid electrochemical oxidation of solutes. Electrode surface increase and catalysis (Park and Zeikus, 2003) or mediator addition (Roller et al, 1984) would be the necessary modifications to improve this situation. The reverse process can also be envisaged at a cathode.…”
Section: Bes and Microbial Ecology In The Natural Environmentmentioning
confidence: 99%
“…An increase of the potential beyond the normal biological boundaries indicates inability of the bacteria to provide electrons at a sufficient rate to avoid electrochemical oxidation of solutes. Electrode surface increase and catalysis (Park and Zeikus, 2003) or mediator addition (Roller et al, 1984) would be the necessary modifications to improve this situation. The reverse process can also be envisaged at a cathode.…”
Section: Bes and Microbial Ecology In The Natural Environmentmentioning
confidence: 99%
“…These different performances of the MFC in the four kinds of electrodes could be realized from the images of micro-surface morphology by using SEM. Comparison of the power generation in this study with other research on the E. coli MFC with the same kinds of electrodes [15], [19]. The power density produced in the MFC system in this study is better than in other previous research.…”
mentioning
confidence: 51%
“…Park et al, [14] reported that the performance of an E. coli MFC was 1.41μA/cm 2 and could achieve up to 3.1μA/cm 2 in current density output by using a modified graphite electrode with Neutral Red. Additionally, Park and Zeikus, [15], [16] designed both NR-woven graphite and Mn (IV) graphite electrodes that served as mediators in their MFC reactors. Doping ions such as Fe (III) and/or Mn (IV) in the cathode also catalyzed the cathode reactions resulting in improved generation of electricity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…이러한 화학적 생산법에 비해 생산수율을 높이고 정제비용을 절감하고자 유산균을 이용하여 mannitol만을 생산하는 연구 가 진행되었으며 (Wisselink et al, 2002;Carvalheiro et al, 2011), 또한 대장균을 이용하여 glucose를 직접 mannitol로 전 환하는 기술도 시도되었다 (Kaup et al, 2005). 이 외에도 고정 화 MDH와 NAD(P)H 조효소의 재순환 방법을 이용하여 fructose를 mannitol로 전환하는 효소생산 기술이 연구되었다 (Slatner et al, 1998;Park and Zeikus, 2003). MDH는 NAD(P) + 를 조효소로 이용하여 mannitol을 fructose로 산화시키거나 반 대로 NAD(P)H를 사용하여 fructose를 mannitol로 환원시키는 dehydrogenase/reductase (DR) family에 속하는 효소이다 (Slatner et al, 1998(Slatner et al, , 1999.…”
unclassified